Synthesis and characterization of PMMA-grafted-ZrO2 hybrid nanoparticles - Nguyen Thi Dieu, Linh; Nguyen Thi Kim, Dung; Dam Xuan, Thang; Do Quang, Tham (Vietnam Journal of Science and Technology, 2023)
In this study, we reported a facile synthesis and the characterization of PMMA-grafted ZrO2 hybrid nanoparticles from original ZrO2 (oZrO2) nanoparticles. The synthesis process included of three steps: (i) modification of nano ZrO2 with a vinyl silane agent, (ii) graft copolymerization of methyl methacrylate (MMA) monomers and modified ZrO2 (mZrO2) nanoparticles, and (iii) extraction of homo PMMA to obtain the final product of PMMA-g-ZrO2 (gZrO2) nanoparticles. Fourier transform infrared (FTIR) spectra and thermogravimetric analysis (TGA) of mZrO2, oZrO2, and gZrO2 indicated that the silane coupling agent was grafted onto oZrO2 nanoparticles. FTIR spectra of gZrO2 indicated PMMA had been successfully grafted onto the surface of ZrO2 nanoparticles. Using TGA method, the PMMA grafting content onto ZrO2 nanoparticles was evaluated as 9.03 wt.%. The electron microscopy (SEM) images of gZrO2, mZrO2, and oZrO2 indicated that their primary particle size and shape were almost unchanged after modification processes, their particle size was in the range from 50 nm to 140 nm. XRD analysis showed the monoclinic crystalline structure of three kinds of ZrO2 nanoparticles (nanocrystals). The organic gZrO2 nanoparticles can be a better candidate as an opacifier additive for polymer nanocomposites or acrylic bone cement.